Foklore: Enhancing Character Education in EFL Classroom - Antika, Rindilla; Asfina, Risda; Sukma, Doris; Nurmayasari, Dewi (Pendidikan Bahasa Inggris (Universitas Internasional Batam), 2024)
Folklore, as a significant component of literature, is extensively utilized in foreign language teaching within classroom settings. Integrating character education into the classroom is essential for holistic student development. This study aims to provide a comprehensive examination of the criteria for selecting appropriate folklore as well as to identify effective strategies for implementing folklore integrated with character education. This research adopts a conceptual approach to explore the use of folklore integrated with character education, addressing the what, why, and how aspects. This topic remains underexplored in the existing literature. The effective strategies for incorporating folklore and character education in English language classes, including interactive storytelling, role-playing, writing prompts, reading folklore, and research projects. The study concludes that integrating folklore and character education can lead to a holistic educational experience that enhances both language proficiency and cultural awareness. The implications suggest that educators should integrate the implementaion of folklore in the class to achieve target language and moral values objectives effectively.